2013
DOI: 10.1039/c2cs35294j
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition-induced elasticity of α-helical bioelastomeric fibres and networks

Abstract: Natural elastomeric fibres play central structural and functional roles in a variety of tissues produced by many organisms from diverse Phyla. Most of these fibres feature amorphous structure and their long-range elastic response is well described within the framework of entropic (rubber-like) elasticity. Recently, it has been recognized that long-range reversible deformation can also occur in biomacromolecular fibres or networks that feature significant secondary structure and long-range order. Their elastome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 152 publications
(224 reference statements)
2
84
0
1
Order By: Relevance
“…The whelk egg capsule is a robust proteinaceous biopolymer, and studies have found that it possesses an a-helical coiled-coil structure (wide-angle X-ray scattering, sequencing of proteins) and shows multiple laminate sheets of ordered fibrils with periodicities 50 nm [219,222,223], which is structurally analogous to the a-keratinous materials [18,224]. At the nanoscale, the capsule wall shows distinct structural features: it consists of cross-plied or slightly misoriented sheets of protein fibrils (Fig.…”
Section: Whelk Egg Capsulesmentioning
confidence: 99%
See 2 more Smart Citations
“…The whelk egg capsule is a robust proteinaceous biopolymer, and studies have found that it possesses an a-helical coiled-coil structure (wide-angle X-ray scattering, sequencing of proteins) and shows multiple laminate sheets of ordered fibrils with periodicities 50 nm [219,222,223], which is structurally analogous to the a-keratinous materials [18,224]. At the nanoscale, the capsule wall shows distinct structural features: it consists of cross-plied or slightly misoriented sheets of protein fibrils (Fig.…”
Section: Whelk Egg Capsulesmentioning
confidence: 99%
“…internal energy driven rather than entropy) are assessed [116]. Other coiled coil proteins, such as myosin II and possibly fibrin, also show this transition [18].…”
Section: Two-phase Model For A-keratinmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the pseudo-hexagonal packing of the a-keratin fibres and how this contributes to the scaling (nanometre to millimetre) and composite potential of keratocyte akeratin materials is now realized [6 ,7 ]. The molecular organization of wool makes it a wonderful textile as it exemplifies phase transition (a-helix to b-sheet [8]) induced elasticity of its component keratin fibres when they are axially stretched [9]. This was first observed and documented by Astbury [4] and subsequently studied in more detail to reveal the importance of coiled-coil sliding and disulphide bonding to the biomechanical properties of hair [10,11].…”
Section: Hard A-keratin -Where It All Beganmentioning
confidence: 98%
“…An ideal elastomer is fully entropic (f em = f s ) because f ie = 0, and a predominantly entropic elastomer is defined as f ie /f em < 0.5. This ratio for elastin is 0.26 and for natural rubber it is 0.18 (316,464). Gravity, in the form of a weight, can be used to stretch a tissue in vitro but, in this case, gravity acts as an aid to examine the net electromagnetic force within the tissue.…”
Section: Vsm-a Smart Materialsmentioning
confidence: 99%